Transforming Polycotton Textile Waste into New Bicomponent Fibers: An Investigative Study - Simon Kronberg; Behnaz Baghaei (Advances in Polymer Technology)
This study aimed to develop an innovative recycling method for end-of-life polycotton textiles, eliminating the need for component separation. The use of 1-ethyl-3-methylimidazolium acetate ([EMIM][Ac]) as an ionic liquid solvent facilitated the dissolution of cotton, enabling the creation of a spinning dope containing cellulose and polyester fibers. Successful spinning of bicomponent fibers ensued, followed by comprehensive fiber evaluation. The dissolution of cotton was achieved with [EMIM][Ac], and spinning trials were conducted to devise a suitable method for regenerated cellulose. Tensile tests on the produced cellulosic fibers clearly demonstrated an increase in tensile strength with higher cellulose concentration. The introduction of polyester fibers to the spinning dope, comprising [EMIM][Ac] and cotton, posed challenges to the entire spinning process. Tensile tests on the resulting bicomponent fibers revealed a decrease in tensile strength compared to pure regenerated cellulose fibers. This reduction was attributed to increased voids and irregular polyester fiber distribution, corroborated by microscopy images and a wicking test. It was concluded that the quantity and length of polyester fibers significantly influenced the tensile strength of the bicomponent fibers, with lower concentrations and shorter fibers resulting in higher strength.